Time course of neuropathologic changes in hyperhomocysteinemia‐induced VCID. (December 2021) - Weekman, Erica M; Lee, Tiffany; Price, Brittani R; Woolums, Abigail E; Hawthorne, Danielle; Seaks, Charles E; Wilcock, Donna M
Abstract: Background: Vascular contributions to cognitive impairment and dementia (VCID) have been increasingly recognized as a leading cause of dementia along with Alzheimer's disease (AD) and is frequently found co‐morbid with AD pathologies. While there is currently no treatment for VCID pathologies such as brain arteriolosclerosis, several modifiable risk factors including hypertension have been identified to reduce the risk of developing VCID. A major, yet under‐appreciated, modifiable risk factor for VCID is hyperhomocysteinemia (HHcy). While it is understood that HHcy, which occurs when plasma homocysteine (a non‐protein forming amino acid) is elevated, has been identified as a risk factor for VCID, the mechanistic underpinnings of HHcy‐induced VCID are lacking. Method: We have previously shown that induction of hyperhomocysteinemia (HHcy) via diet in both wildtype (WT) and APP/PS1 mice produces cerebrovascular pathologies. While the pathological characteristics of HHcy have been identified in both models, the time course for these changes is unclear. We examined neuropathological changes along a time course of 2, 4, 6, 10, 14 and 18 weeks on diet in our models. Result: In both the WT and APP/PS1 mice on the HHcy diet, increased microglial staining and significant increases in several pro‐inflammatory markers was noted after 6 weeks on diet. Several astrocytic end feet markers were significantly decreased at 10 weeks in the WT mice on HHcy diet. Cognitive decline also began at 10 weeks on diet in both models. Prussian blue staining revealed a significant increase in microhemorrhages starting at 14 weeks on the HHcy diet. Finally, in the co‐morbidity model, induction of HHcy resulted in redistribution of amyloid from the parenchyma to the vasculature starting at 14 weeks on diet. Conclusion: Overall, induction of HHcy in both WT and APP/PS1 mice leads first to neuroinflammation, followed by astrocytic end foot disruption and cognitive decline, and finally, microhemorrhages, and redistribution of amyloid to the vasculature in the APP/PS1 mice. Taken together, this data suggests that neuroinflammation is an initiator in HHcy mediated VCID alone and when amyloid plaques are present, providing a possible common target for therapeutics in both VCID and co‐morbid patients.